(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study is to estimate the time to deploy containerized applications using novel kubernetes based microservice architecture over VMware workstation based virtualization architecture. Materials and Methods: Sample groups that are considered in the project can be classified into two each has 20 samples, one for Microservice architecture and other for Virtualization architecture, which are tested using 0.80 for G-power to determine the sample size and for t-test analysis. 20 containerized applications have been used in each group for estimating deployment time. Results: The azure kubernetes based feature of Microservice architecture with efficient accuracy of 60%, which by far seems to be better than the Virtualization architecture which gives around 54.40%. The significance is around 0.482 (p<0.05) and therefore there is a statistical insignificant difference among the study group. Conclusion: Novel Kubernetes based microservice architecture seems to be better in deploying containerized applications over the VMware workstation based virtualization architecture.